The P2X7 receptor–inflammasome complex has a role in modulating the inflammatory response in primary Sjögren's syndrome. (17th August 2013) - Baldini, C.; Rossi, C.; Ferro, F.; Santini, E.; Seccia, V.; Donati, V.; Solini, A.
Abstract Objective Innate and adaptive immunity may contribute to gland dysfunction in patients with primary Sjögren's syndrome (pSS). The P2X7 receptor (P2X7R)–NLRP3 inflammasome complex modulates the release of the inflammatory cytokines IL‐1β and IL‐18. The presence of P2X7R in salivary glands suggests an interesting scenario for the initiation and amplification of the innate immune response in pSS. Therefore, the aim of this study was to assess the role of the P2X7R–NLRP3 inflammasome in pSS. Subjects and Methods Twenty‐one consecutive patients with pSS according to the American–European Consensus Group criteria and 15 patients with sicca syndrome (i.e. without Sjögren's syndrome, non‐SS) were enrolled in this study, together with six control (CTL) subjects. Expression of the P2X7R‐NLRP3 platform and IL‐18 was determined by real‐time PCR and western blotting in gland specimens and peripheral lymphomonocytes; data were related to patients92 clinical, serological and histopathological characteristics. The presence of IL‐18 was determined in gland and saliva samples. Results P2X7R expression was significantly higher in salivary glands from individuals with pSS than in those from non‐SS and CTL subjects. Accordingly, the gene expression levels of the inflammasome components NLRP3, ASC and caspase‐1 were significantly higher in pSS gland specimens, and this was paralleled by an increased expression of mature IL‐18 in pSS saliva samples. The expression of both the P2X7R and the inflammasome components was a marker of disease‐related glandular involvement, being increased in patients with anti‐Ro/SSA positivity and correlated with focus score. Conclusion The results of this study suggest an involvement of the P2X7R–inflammasome–caspase‐1–IL‐18 axis in the development of pSS exocrinopathy. This finding provides the basis for studying the complex mechanisms underlying pSS, as well as for developing novel potential therapeutic strategies.